2020
DOI: 10.3390/ijerph17124599
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Seasonal PM2.5 Samples and Their Cytotoxicity in Human Lung Epithelial Cells (A549)

Abstract: In order to study the toxicity of fine particulate matter (PM2.5) sourced from different seasons on human health, we collected PM2.5 samples quarterly from March 2016 to February 2017 in Nanjing, China. The component analysis results showed that high proportions of water-soluble organic carbon (WSOC), SO42−, Ca2+ and Mg2+ were found in the summer samples, while high proportions of NO3−, NH4+ and heavy metals were observed in the spring and winter samples. Then human lung epithelial cells (A549) were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The production change of these VOC species might be caused by reactive oxygen species (ROS). The toxicological results indicated that ROS production was significantly correlated with NO 3 − , NH 4 − , and water-soluble organic matter in PM, 40,41 which could play an important role in the change in exhaled VOCs. In this work, the PM 2.5 levels ranged from 6.58 μg/m 3 to more than 100 μg/m 3 and PM 10 levels ranged from 30.08 to 224.35 μg/m 3 .…”
mentioning
confidence: 97%
“…The production change of these VOC species might be caused by reactive oxygen species (ROS). The toxicological results indicated that ROS production was significantly correlated with NO 3 − , NH 4 − , and water-soluble organic matter in PM, 40,41 which could play an important role in the change in exhaled VOCs. In this work, the PM 2.5 levels ranged from 6.58 μg/m 3 to more than 100 μg/m 3 and PM 10 levels ranged from 30.08 to 224.35 μg/m 3 .…”
mentioning
confidence: 97%
“…The high SNA concentrations in PM 2.5 samples from 2015 to 2019 indicated relatively severe secondary pollution around the sampling sites. The ratio of NO 3 - concentration to SO 4 2- concentration is often used to identify whether NO x and SO 2 in the atmosphere come from mobile or fixed sources [ 35 ]. If the ratio is greater than 1, the emission sources are dominated by mobile sources (e.g., vehicle exhaust) and conversely by fixed sources (e.g., coal combustion).…”
Section: Resultsmentioning
confidence: 99%
“…Other trace elements such as Ba, Bi, Cd, Co, Cr and Cs were present at low levels, accounting for about 5.3–6.2% of the total amount analysed. Of these, Fe and Al—as crustal elements—were mainly derived from soil and dust, while the presence of high proportions of Zn, Cu, Pb and Mn detected in PM 2.5 and PM 1 samples may be directly related to vehicle emissions due to the proximity of sampling points to high-traffic-flow paths [ 48 ]. Cu and Pb mainly originated from motor vehicle emissions and industrial emissions, and both showed similar trends in the proportion of PM 2.5 and PM 1 samples.…”
Section: Resultsmentioning
confidence: 99%